Social Capital and Internet - Žiliukaitė, Rūta (Sociologija. Mintis ir veiksmas, 2004)
The article presents review of four theoretical approaches to impact of Internet on social capital, namely, „internet as destroying social capital”, „internet as having no consequences for social capital”, „internet as transforming social capital” and „internet as supplementing social capital”. After introducing main arguments of each approach, an attempt is made to evaluate their capacity to describe and explain an influence of internet use on social relationship and civic participation. Author argues that the most promising notion of internet in both respects is that of “internet as supplementing social capital”. Internet provides effective tools for facilitating maintenance and formation of social capital, given that condition of development of human skills and knowledge how to integrate internet into their social activities, positive experience, and interpersonal and institutional environment that encourage using internet and provide necessary support in it are met.